Improving The Performance of the Image Captioning Systems Using a Pre- Classification Stage: تحسين أداء أنظمة وصف الصور باستخدام مرحلة التصنيف المسبق للصور - Rasha Mohammed Mualla, Jafar Alkheir, Samer Sulaiman (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
In this research, we introduce a novel image classification and captioning system by adding a classification layer before the image captioning models. The suggested approach consists of three main steps and inspired by the state- of- art that generating image captioning inside small sub- classes categories is better than the unclassified large dataset. In the first one, we have collected a dataset of two international datasets (MS- COCO and Flickr2k) including 10778 images in which 80% is used for training and 20% for validation. In the next step, dataset images have been classified into 11 classes (10 classes of indoor and outdoor categories and one class of "Null" category) and fed into a deep learning classifier. The classifier is re- trained again using our classes and learned to classify each image to the corresponding category. At the final step, each classified image is used as input of 11 pre- trained classified image captioning models, and the final captioning sentence is generated. The experiments show that adding the pre- classification step before the image captioning stage improves the performance significantly by (8.15% and 8.44%) and (12.7407% and 16.7048%) for Top- 1 and Top- 5 of English and Arabic systems respectively. The classification step achieves a true classification rate of 71.32% and 73.09% for English and Arabic systems respectively.